O professor/gestor universitário de instituição pública federal: fazeres e saberes implicados nas arquitetônicas docentes - Dewes, Andiara (2023)
This research is characterized as sociocultural narrative research. The focus thematic is teaching activity, university management, teacher/manager architecture in emerging contexts in Brazilian higher education. The general objective is to understand the implications of teaching activities in the constitution of the teacher/manager's architecture. The context of the investigation is a public university in the interior of Southern Brazil and the subjects are professors/managers at this university. The development of the research was organized with two immersions in the investigated field: the first results in a descriptive study on institutional architecture, through which we present how the researched institution organizes and institutionally recognizes the performance of professors in management/leadership positions, highlighting - the absence of workload in/from management in the calculation of teaching duties and the different performance profiles of teachers in the teaching, research, extension and management dimensions; the second immersion was carried out through narrative interviews with teachers/managers. Through the interpretative-explanatory process, it was consolidated as an architectural category of the university teacher/manager, consisting of the elements, categories, trajectories, dimensions of teaching and production of actions and knowledge of/in management and as transversal elements there are emerging contexts. It is observed that the constitution of the teaching architecture of the university professor/manager happens in the daily work as a manager. Through a labyrinthine experience, the teacher, upon assuming a management/leadership position, faced with an institutional architecture and a university culture already constituted and instituted, begins to experience tension between the well-being and discomfort of the teacher in the face of all the implications that this action reverberates in the organization and constitution of his teaching. In a situation in which he experiences different teaching feelings, such as helplessness and institutional loneliness, teaching vulnerability, teaching anguish, teaching frustration, the teacher/manager, in order to learn the ropes of management, relies on former managers and administrative employees, therefore in the emerging nuances of an informal knowledge network and shared knowledge about management. Given the absence of institutional monitoring of the teaching career, we demonstrate that acting as a manager is driven by institutional architecture, institutional dynamics and university culture. Such aspects lead the teacher to produce activities in/from management and, although in an incipient way, he produces knowledge; Along with this, nuances of teaching resilience and pedagogical alternation are evident. Thus, in the constitution of teaching architecture there is the influence of both institutional architecture and the being/being/doing, without alibis, of the teacher in the face of the possibilities of activities that come to him at the university.